2004
DOI: 10.2202/1558-3708.1155
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Monetary Policy Rules: Some New Evidence for the U.S.

Abstract: This paper dreives optimal monetary policy rules in setups where certainty equivalence does not hold because either central bank preferences are not quadratic, and/or the aggregate supply relation is nonlinear. Analytical results show that these features lead to sign and size aymmetries, and nonlinearities in the policy rule. Reduced-form estimates indicate that US monetary policy can be characterized by a nonlinear policy rule after 1983, but not before 1979.This finding is consistent with the view that the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 24 publications
11
117
1
3
Order By: Relevance
“…In the Bank of England there were 50 dissents in this situation: 29 in favor of keeping the interest rate unchanged and 21 in favor of a policy in the same direction as that adopted by the committee but of a usually larger magnitude. 8 In the Riksbank, there were 17 dissents in meetings where the EB agreed to adjust the interest rate: 11 were in favor of keeping the Repo rate unchanged and 6 in favor of a change in the same direction as that chosen by the committee (in two cases of a smaller magnitude and in four cases of a larger magnitude).…”
Section: Voting Recordsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Bank of England there were 50 dissents in this situation: 29 in favor of keeping the interest rate unchanged and 21 in favor of a policy in the same direction as that adopted by the committee but of a usually larger magnitude. 8 In the Riksbank, there were 17 dissents in meetings where the EB agreed to adjust the interest rate: 11 were in favor of keeping the Repo rate unchanged and 6 in favor of a change in the same direction as that chosen by the committee (in two cases of a smaller magnitude and in four cases of a larger magnitude).…”
Section: Voting Recordsmentioning
confidence: 99%
“…However, in the case of the FOMC, the highest average number of dissenting votes takes place when the committee lowers the interest rate. 8 For example, in the MPC meeting on 5 April 2001, the committee agreed to cut the interest rate by 25 basis points but two members dissented in favor of a larger cut of 50 points. [5] has been changed but the dissenter would prefer an even larger change.…”
Section: Voting Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this structural approach are much more scarce, however, and seem limited to Dolado et al (2004) and Surico (2003Surico ( , 2004. Dolado et al (2004) have shown that an asymmetric loss function of the linex functional form and a macroeconomic structure of the Rudebusch-Svensson type Svensson, 1999, 2002) generate an optimal policy reaction function that includes the conditional variance of inflation in addition to the standard reaction function regressors.…”
Section: The Case For Asymmetric Monetary Policymaker's Preferencesmentioning
confidence: 99%
“…Cukierman and Gerlach (2003), Ruge-Murcia (2003), Dolado et al (2004Dolado et al ( , 2005, and Surico (2007a,b) have shown evidence supporting asymmetries by adopting a monetary policy reaction function that feature asymmetries in either inflation or the output gap for the US, UK, EU and OECD countries. Boinet and Martin (2008) also implemented a monetary policy reaction function that feature asymmetries and zone-like behaviours for the UK and found the evidence of zone-like responses to inflation.…”
Section: Introductionmentioning
confidence: 99%